(untitled) (Research, Society and Development, 2022)
Aim: To compare clinical and microbial profiles in type 2 diabetic (DM) and non-diabetic (NDM) patients with chronic periodontitis after non-surgical periodontal therapy. Methods: 30 subjects with periodontitis were separated into two groups: 15 DM and 15 NDM. Blood parameters and clinical parameters were assessed. Subgingival biofilm samples were collected from periodontal pockets (PD > 5mm) and ckecked by the presence of Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Tannerella forsythia (Tf), Prevotella intermedia (Pi), Campylobacter rectus (Cr), Candida albicans (Ca), Candida glabrata (Cg), Candida tropicalis (Ct), Candida dublinienses (Cd) by Polymerase Chain Reaction. Data were statistically analyzed, considering p < 0.05. Results: PI, PD, and CAL significantly reduced after 3 months of periodontal therapy in both groups. Only levels of HbA1c reduced in the DM group after 3 months. Comparisons between baseline and 3 months after periodontal therapy revealed a reduction of Aa, Pg, Tf, Pi, Ct and Cd for the NDM group and Aa, Pg, Tf, and Ca for the DM group. Conclusions: The periodontal therapy was effective in reducing clinical parameters and microbial levels, regardless the presence of the diabetes mellitus. However, high levels of Candida ssp. remained in periodontal pockets of diabetic patients even after therapy.